Hadith #3462 - Sunan al-Nasa'i - Habiba bint Sahl bin Tha'laba; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Umarh bint 'Abdur Rahman عمرة بنت عبد الرحمن بن سعد بن زرارة; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan al-Nasa'i)
“The Prophet swore an oath of abstention from his wives for a month and stayed in his room for twenty-nine days. It was said: ‘O Messenger of Allah, did you not swear an oath of abstention for a month?’ He said: ‘This month is twenty-nine days.'”
Grade:

Hadith #2226 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Habiba bint Sahl bin Tha'laba; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If any woman asks her husband for divorce without some strong reason, the odour of Paradise will be forbidden to her.
Grade: Sahih